Proses Rekrutmen dan Kompetensi terhadap Kinerja Karyawan PT. Bumi Mineral Sulawesi Kabupaten Luwu - Armah Suratmah; Suhandra Makkasau; Samsul Bachri (Universitas Batanghari Jambi, 2023)
This research aims to understand the recruitment process and competencies regarding the performance of PT employees. Bumi Mineral Sulawesi, Luwu Regency, this research was carried out from January 5 - January 13 2023. Sample determination used the Slovin formula which obtained 50 samples to represent 1000 populations. The method in this research uses the causality method with a qualitative approach, data collection analysis in this research uses primary data by distributing questionnaires to respondents, data processing in this research is assisted by the SPSS version 22 application. The results of partial statistical calculations for the recruitment process variables can be seen that the value sig 0.000 < 0.05 and t-count > and t-table value, namely -0.2770> 2.012; meaning that the recruitment process has a negative effect on the performance of PT employees. Bumi Mineral Sulawesi, Luwu Regency, and for the competency variable, it shows that the sig value is 0.225>0.05 and the t-count is > the t-table value, namely 1.152<2.012, meaning it has no positive effect on PT's performance. Sulawesi Mineral Earth, Luwu Regency. Testing the influence of the independent variables simultaneously using the F test obtained a sig value of 0.028 <0.05 F-count of 3.842 > F-table of 3.19. So it can be concluded that the recruitment process has a partial negative effect on employee performance, the Competency variable has no partial effect. Meanwhile, the recruitment process and competency simultaneously influence the performance of PT employees. Sulawesi Mineral Earth, Luwu Regency.